Dynamic modeling of fundamental converters - Li, Yi. (2011)
A DC/DC converter is a class of power converter. The electronic circuit is designed to convert the unregulated dc input into a controlled dc output that is equal to desired level. The switching converter is the converter that consists of a number of storage elements and switches. The switches in the circuit action periodically to control the dynamic transfer of power from the input to output. The two fundamental switching converters are the buck converter and the boost converter. The Ćuk converter is a derivative of the buck-boost converter that combines the buck and boost converters. This project intends to deduce the equations to describe the three converters, then modeling them by using MATLAB. From the simulation, it can be found how the elements in converters influence the output waveform. DC/DC converters are widely used in industrial applications. Therefore, it is necessary to understand their characteristics.